Memorial do Convento: caminhos para uma nova leitura do romance histórico - Larêdo, Filipe Nassar (2019)
In his novel Memorial do Convento, the writer José Saramago proposes a new outlook for the historical facts that involved the construction of the National Palace of Mafra, in the early 18th century, in Portugal. Saramago chooses the king and the queen to initiate the narrative, but treats them in a satirical way that displaces them from protagonism, while marginal characters emerge from common people to gain prominence in the narrative. Due to this redesign, it seems possible to associate Memorial do Convento with something that goes beyond what is traditionally considered a historical novel. The construction of the protagonists, allowing access of ordinary individuals to the status of heroes, is marked by tragic effects that echo the Greek theater, and our objective is to identify aspects like these, which express differentiation in relation to the traditional concept of historiographical romance. With this in mind, we contemplate the "romantic view" as presented by the philosopher Benedito Nunes, and take into consideration the concept of historical novel according to the theoretical proposals of scholars like György Lukács, Alcmeno Bastos, Avrom Fleishman, and Maria de Fátima Marinho. We also ponder Nietzsche's appreciation of art as a means of constructing reality, and the relationship between Apollonian and Dionysian pointed out by the German philosopher in Greek tragedy. Finally, we compare the subjectivization of historical facts observed in Memorial do Convento with the foundations of tragedy in the Greek theater, in the light of studies by Jacques Rancière, Terry Eagleton, Albin Lesky and Jean-Pierre Vernant